The relationship between sleep duration, BMI and optimism levels in generation Z students - Biber, Duke; Czech, Daniel; Donald, Ellen; Hassett, Anna; Tucker, Allison (Journal of Interdisciplinary Studies in Education, 2022)
In this study, we examine the relationship between sleep duration and reported levels of optimism in Generation Z (i.e., born after 1996) students aged 17 to 24. This study hypothesizes that optimism and duration of sleep will have a statistically significant positive relationship. Participants in this study are Generation Z college students located in the Southeastern United States. The sample consisted of 1562 students enrolled in a required physical activity class. A Pearson’s correlation determined that there was a statistically significant positive relationship between sleep and optimism. Research implications and future research trends on sleep and optimism are discussed.